On the effects of the number of baffles in sloshing dynamics - Korkmaz, Fatih C.; Guzel, Bulent (TAYLOR & FRANCIS LTD, 2023)
This study examines the effect of the number of perforated baffles in sloshing phenomenon in a partially filled tank. The natural frequencies in one-, two- and no-baffle cases are experimentally obtained; change in natural frequencies and reduction in sloshing impacts due to baffles are reported. It is observed that adding the second baffle has a minor effect in damping the sloshing loads at non-resonance frequencies in comparison to ones obtained in one-baffle sloshing tests. Although the natural frequency is significantly increased and pressure distribution profile is altered at higher oscillation frequencies in two-baffle case, the significant reduction in peak pressure values is observed at the frequencies near the natural frequency in one-baffle case. The results indicate that the number of the baffles should be optimised considering the natural frequency of the carrier and external excitation frequencies for the purpose of weight minimisation, fast loading and unloading of the tanks.
Keywords: Sloshing; perforated baffles; wave impact; surging; RECTANGULAR TANK; IMPACT PRESSURE; WAVE IMPACTS; Engineering